Speaking Skills Talk Show: Building Public Speech For Gen-Z Tadris Bahasa Indonesia UIN Gusdur - Rissa Shofiani; Baqyiyatul Izzah; Rizky Bagus Satriyojati; Usnidatillah Usnidatillah; Tasfiyatun Nuria (Pendidikan Bahasa dan Sastra Indonesia, 2024)
Based on observations in the academic community of Tadris Bahasa Indonesia UIN K.H. Abdurrahman Wahid Pekalongan, the majority of students still experience difficulties in public speaking, this encourages the lecturer team to provide solutions in the form of speaking skills talk shows for students majoring in Tadris Bahasa Indonesia. The purpose of this activity is to improve public speaking skills for students. A total of 85 participants in this activity, the implementation of the service program was carried out in the context of developing and strengthening student speaking skills. The method used is qualitative with a description approach. The results of this activity show that most students still experience difficulties in public speaking but this program helps them understand strategies to overcome challenges in public speaking skills. It is hoped that this activity will be the first step for students to continue to hone their speaking skills, to be more courageous and able to have a positive impact, both for themselves, the academic environment, and society.